PENYULUHAN EDUKASI BAHAYA NARKOTIKA OLEH TIM KKN KEBANGSAAN PADA SISWA KELAS 1 SMA NEGERI 1 LEDO : PENYULUHAN EDUKASI BAHAYA NARKOTIKA OLEH TIM KKN KEBANGSAAN PADA SISWA KELAS 1 SMA NEGERI 1 LEDO - Antonius Anton; Totok Victor Didik Saputro (Jurnal Pengabdian Masyarakat Nusantara, 2023)
According to the World Health Organization (WHO), adolescents are individuals aged between 10 to 19 years old. Adolescents themselves refer to emotional and behavioral characteristics that tend to fluctuate. In their transitional period, adolescents have a very large curiosity about the life around them. One of the juvenile delinquencies that is quite prevalent in today's life is drug abuse. This can happen, among other things, because there are several unresolved conflicts during childhood, resulting in rebellion and opposition that leads to drug use in abnormal doses. Narcotics themselves are substances or drugs that can cause decreased consciousness, loss of sensation, reduced to eliminate pain, and cause a sense of dependence. One of the first steps to prevent drug abuse is to provide education to adolescents so that they have maximum provisions in facing challenges in the future.